Boron-modulated surface of hollow nickel framework for improved hydrogen evolution. Issue 19 (5th February 2021) - Gu, Weishi; Pan, Zhongqin; Tao, Han; Guo, Yanling; Pu, Jun; Zhong, Chenglin; Li, Jiachen; Ye, Changqing; Zhou, Qingwen
Abstract : Taking advantage of micro/nano structure engineering and surface boron modulation, we developed a binder-free and support-free electrode to enrich and optimize active sites of Ni. Abstract : A hollow Ni framework (HNF) is designed and prepared to utilize the exterior and interior surface active sites of a Ni-based binder-free and support-free electrode. Furthermore, the more efficient Ni–B active sites are then in situ introduced on the surface of HNF. This micro/nano structure engineering, together with the surface boron modulation, results in a synergistically enhanced catalytic effect for the HER performance.